Levosimendan Efficacy and Safety: 20 years of SIMDAX in Clinical Use - Papp, Zoltán; Agostoni, Piergiuseppe; Alvarez, Julian; Bettex, Dominique; Bouchez, Stefan; Brito, Dulce; Černý, Vladimir; Comin-Colet, Josep; Crespo-Leiro, Marisa G; Delgado, Juan F; Édes, Istvan; Eremenko, Alexander A; et al. (Cardiac failure review, 2020)
Levosimendan was first approved for clinic use in 2000, when authorisation was granted by Swedish regulatory authorities for the haemodynamic stabilisation of patients with acutely decompensated chronic heart failure. In the ensuing 20 years, this distinctive inodilator, which enhances cardiac contractility through calcium sensitisation and promotes vasodilatation through the opening of adenosine triphosphate-dependent potassium channels on vascular smooth muscle cells, has been approved in more than 60 jurisdictions, including most of the countries of the European Union and Latin America. Areas of clinical application have expanded considerably and now include cardiogenic shock, takotsubo cardiomyopathy, advanced heart failure, right ventricular failure and pulmonary hypertension, cardiac surgery, critical care and emergency medicine. Levosimendan is currently in active clinical evaluation in the US. Levosimendan in IV formulation is being used as a research tool in the exploration of a wide range of cardiac and non-cardiac disease states. A levosimendan oral form is at present under evaluation in the management of amyotrophic lateral sclerosis. To mark the 20 years since the advent of levosimendan in clinical use, 51 experts from 23 European countries (Austria, Belgium, Croatia, Cyprus, Czech Republic, Estonia, Finland, France, Germany, Greece, Hungary, Italy, the Netherlands, Norway, Poland, Portugal, Russia, Slovenia, Spain, Sweden, Switzerland, UK and Ukraine) contributed to this essay, which evaluates one of the relatively few drugs to have been successfully introduced into the acute heart failure arena in recent times and charts a possible development trajectory for the next 20 years.
Keywords: advanced heart failure; inodilator; Acute heart failure; regulatory clinical trial; haemodynamics; inotrope; neurohormone